First record of Scolia rufiventris Fabricius, 1804 (Hymenoptera: Scoliidae) from Pantanal, Brazil - Aranda, Rodrigo (Entomological Communications, 2021)
The first record of the wasp Scolia rufiventris Fabricius, 1804 is reported for the state of Mato Grosso do Sul and the Brazilian Pantanal in the Abobral region, in an area with predominance of flooded fields and Cambarazal dominance. The registration of the species contributes to the knowledge of the diversity of insects in the Pantanal, mainly in view of the last events of devastation by large-scale fires.